Acknowledgement to Authors, Reviewers and Editors of Cardiology and Cardiovascular Medicine in 2017-2018. - Office, Editorial; Journals, Fortune (Cardiology and Cardiovascular Medicine, 2019)
Rigorous peer-review is the main part in building the corner-stone of high-quality academic publishing. The editorial team greatly appreciates the authors, reviewers who contributed their knowledge and expertise to the journal’s editorial process over the past 12 months. In 2017, a total of 30 articles were published in the journal, with a median time to first decision of 15 days and a median time to publication of 20 days. The editorial office would like to express their sincere gratitude to the following authors, reviewers and editors for their cooperation and dedication in 2017